Irreversible Electroporation: Expanding the Armamentarium against Pancreatic Cancer - Lyons, Gray R.; Schiro, Brian J.; Narayanan, Govindarajan (Digestive Disease Interventions, 2019)
Locally advanced pancreatic cancer is often refractory to conventional therapy, thus warranting new approaches. Irreversible electroporation is an ablative modality that has the potential to deliver targeted anticancer treatment with minimal damage to surrounding structures. Indications for irreversible electroporation in pancreatic cancer patients include palliation for metastatic disease, downstaging for surgery in locally advanced disease, and treatment of local recurrence following operative resection. Benefits of the modality in pancreatic cancer include a minimally invasive approach, precise delivery that minimizes nontarget ablation, and upregulation of anticancer immune response. Early studies have demonstrated an acceptable safety profile for irreversible electroporation; however, more data are needed to define the role of IRE in the treatment algorithm of pancreatic cancer.
Keywords: pancreatic cancer; electroporation; chemotherapy